Collage in Twentieth-Century Art, Literature and Culture : Joseph Cornell, William Burroughs, Frank O'Hara, and Bob Dylan /: Joseph Cornell, William Burroughs, Frank O'Hara, and Bob Dylan. (2016) - Unknown
No abstract available